The Views and Roles of Coaches in Youth Athlete Motivation: A Qualitative Approach - Kristin L. Zomermaand (Pamukkale University, 2010)
The coach's influence on youth sport motivation and adherence to sport has been studied previously (Conroy and Coatsworth, 2007; Smith et al., 2007) mostly from the perspective of the athletes. This study examines the way youth and high school coaches view the motivations of young athletes. Six coaches, identified by their peers as quality coaches, were interviewed. Content analysis of the tape recorded semi-structured interviews revealed several main themes including: coaches' role in encouraging motivation; the balance between praise and accountability; empowering the athletes; building personal relationships with the athletes; and focusing on improvement throughout the season. These themes show support for need satisfaction in self-determination theory and the role of the coach in supporting a task-involved motivational climate.